A nation of peoples a sourcebook on America's multicultural heritage (Greenwood Press, 1999)
Using the latest available materials, expert contributors explore the principal racial, religious, and ethnic groups of the United States. The debate over America's multiculturalism has been intense for nearly three decades, dividing opponents into those insisting on such recognition and those fearing that such a formal acknowledgment will undermine the civic bonds created by a heterogeneous nation. Facts have often been the victim in this dispute, and few works have successfully attempted to present the broad spectrum of America's ethnic groups in a format that is readable, current, and authoritative. This reference book includes alphabetically arranged chapters on more than two dozen racial, religious, and ethnic groups of the United States, including African Americans, American Indians, Filipinos, Hawaiians, Mexicans, Mormons, and Puerto Ricans. Each chapter is written by a leading scholar and overviews the experiences and achievements of a particular group in the United States. Among the topics considered are the group's entry into America; the problems of adaptation faced by the first generation; economic, political, and cultural integration; and the status of the group in contemporary society. Each chapter ends with a thorough bibliographical essay, and the volume concludes with a review of the most important general works in the field.